(untitled) (Fiep Bulletin - online, 2014)
The aim of this study is to check the contents taught by the teachers in the class of Physical Education. It is an exploratory descriptive study. Students from the fifth to the eight grade and two teachers of public schools were analyzed in this work. The data were taken between July to November of 2005 and thirty classes were observed. We used similar schema to the procedures used by Stefanello (1999) to analyze the contents in the classes. In the analysis of the data we used the frequency measurement and the percentage of frequency to the description of the results. Considering the modalities, volleyball (60%) was the most used in all the groups, then soccer indoor (40%). Students have had games in most of the time (34,3%) and technical exercise (28,5%). We’ve observed that part of the time in class was used with the transition among the activities, checking the presence or absence of the students in the class and time spent to drink water. The activities of technical information (63,7%) worry the teachers a lot. We’ve also observed - relating to the conditions of the realization of the tasks - that there’s no sequence relation of content among the exercises in the most of the progressions done. The most frequent teachers’ action was making all the decisions and supervising. We haven’t found any evidence confirming that teachers concern about gradually increasing the execution of exercises and improving specific details. We’ve found that teachers show and develop in the same way the contents in different levels of the elementary school. A traditional pattern has been used.